Pierre Monbeig e o vacilo de uma tradição nos trópicos - César Simoni Santos (Confins)
The considerations here arranged aim at featuring some elements of Pierre Monbeig’s work which reveal the innovative and even revolutionary character of his Geography. Most of these elements appear dispersed and have not been systematized with that purpose throughout his work, but their reappearance in several articles and books suggests their importance as well as the timid intentionality behind each of these recurrent assertions. The intuitive and barely analytical character of some of his strong conclusions regarding the propriety of old concepts and methods of the traditional French Geography already contains the germ and the power of a criticism which became usual only 15 or 20 years later, and this is how they have been considered here. Perhaps for their unsystematic and still fairly intuitive condition, such theoretical-conceptual advances have rarely been debated, if only superficially, and never with its due importance. However, I am confident that the experience of getting acquainted with the Brazilian reality opened for Pierre Monbeig the opportunity for the commencement of a re-elaboration not only of Geography’s theoretical and conceptual outline, but also of its own epistemological status — and this is what I intend to demonstrate here. In these terms, besides the expected “update” of the social theories, which usually occurs in a diachronic perspective, Monbeig had the chance of experiencing, almost simultaneously with the consolidation of the regional method in France, a reality which has an aversion to the stability of special arrangements, which allowed him to seriously inquire the legitimacy of the method which had become a mere routine in the practice of Geography.